Use of the Mitrofanoff principle in urinary tract reconstruction: Experience with 122 children - Sinha Shalini; Sen Sudipta; Chacko Jacob; Karl Sampath; Mathai John (Wolters Kluwer Medknow Publications, 2006)
Purpose: Use of the Mitrofanoff principle is a valuable adjunct to many reconstructive urological procedures in the pediatric age group requiring clean intermittent catheterization (CIC) especially if the urethra is not easily catheterizable. We present our experience with 122 children and analyze the results of this operation. Materials and Methods: 133 Mitrofanoff channels (100 appendicular, 31 ureteric and 2 Monti) were constructed in 122 children (93 boys and 29 girls) of mean age 6.3 years over the period from 1997 to 2005. The procedure was part of the reconstructive procedure in patients of neurogenic bladder (n=44), exstrophy-epispadias (n=40), posterior Urethral valve (n=30), and other diseases (n=8). Additional procedures included augmentation cystoplasty (n=90) and bladder neck procedure (n=46). Results: Mean follow-up was 2.6 years in 109 patients. Overall results were satisfactory. Major complication rates with the Mitrofanoff conduit using appendicular and ureteric channels were 7.4 % in and 25.8%, respectively, most of the ureteric channels due to non-use, there being alternate channels for catheterization. Only six (4.5%) children required re-operation for significant problems with the Mitrofanoff conduit: revision of stoma due to stenosis or kinking (n=4) and closure of stoma due to troublesome leak (n=2). Children and parents were satisfied with the results of the operation and the majority was compliant with regular CIC. All children were socially well accepted and those above 6 years of age were attending regular school. Conclusions: The Mitrofanoff procedure is a feasible and acceptable option, with a low complication rate, for use as part of complex urinary reconstruction in a developing country. Patient education, family motivation, and cost reduction are important factors for success.